Experimental Analysis of a Plume Dispersion Around Obstacles. (December 2015) - Brusca, S.; Famoso, F.; Lanzafame, R.; Garrano, A. Marino Cugno; Monforte, P.
Abstract: Nowadays, transport and deposition of aerosol particles (PM2.5, PM10, TSP) caused by industrial plants, environmental applications and transports, are of great concern to public health. Despite the establishment by the European Union of emission standards (European directive 2008/50/CE e.g) to control the limits of particulates in the air, the emissions by industrial plants are still not accurately monitored. In particular, the interaction between plume dispersion and obstacles, such as buildings, is not currently well studied. A lot of theoretical researches were carried out in this field with a lack of experimental data comparison. This paper focuses on a laboratory work made to better explain the interaction of a continuous plume released from a point source and various obstacles. First of all a vertical pipe was reproduced, a continuous aerosol emitter was characterized in terms of a specified and controlled mass flow and the ratio between smoke emission and the total suspended particulates thanks to use of the certified gravimetric calculation of PM10 . The experimental campaigns were conducted by means of a wind tunnel all the data collected were validated. The characterization of plume was made by the use of several sensors and calculation of velocity in several points of the field. Moreover, the plume dispersion was studied also by using digital image analysis. It was then investigated downwind the influence of obstacles of various shapes and distances from source in terms of aerosol concentration in several points.